2015
DOI: 10.1155/2015/754278
|View full text |Cite
|
Sign up to set email alerts
|

Design and Experimentation of Piezoelectric Crystal Sensor Array for Grain Cleaning Loss

Abstract: In order to improve the accuracy and reliability for detection of grains cleaning loss, a piezoelectric crystal sensor array was proposed in full width of distribution to realize the online multipoints detection. The dynamic model for grain collision sensor array was evaluated by the method of experimental model analysis. The distribution of low-level vibration and deformation was tested for the sensitive elements of detection array using dynamic signal tester. The location and quantity of the piezoelectric cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…However, this behavior indicates that the management of harvester adjustments must be constantly monitored and that they must be changed according to crop conditions to maximize the efficiency of the harvester (Purfürst & Erler, 2011). However, the lack of embedded technology in peanut harvesters makes it challenging to adjust and manage the settings in real time, unlike harvesters for other crops that already have embedded loss sensors (Ni et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…However, this behavior indicates that the management of harvester adjustments must be constantly monitored and that they must be changed according to crop conditions to maximize the efficiency of the harvester (Purfürst & Erler, 2011). However, the lack of embedded technology in peanut harvesters makes it challenging to adjust and manage the settings in real time, unlike harvesters for other crops that already have embedded loss sensors (Ni et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…It was found that the attenuation time of the grain collision signals was shortened to about 3 ms and the maximum signal amplitude was nearly about 4 V when the sensitive plate treated with a partially constrained damping layer in places undergoing larger deformations under the condition of length a = 120 mm, width b = 180 mm, thickness h = 1.0 mm. Compared with other sensors equipped on most commercial harvesters and sensors developed by Ni et al [ 21 ]. which attenuation time was about 1 s, and the maximum signal amplitude was less than 1.2 V, the sensor detection speed was greatly improved.…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of grain collision experiments, we determined an optimal position to lay the damping layer, as shown in Figure 12a . The grain collision signal, shown in Figure 12b , indicated that the attenuation time of the grain collision signal was shortened to about 3 ms, which showed that the sensor could identify more than 300 grains within 1 s in theory; and the sensor has a relative higher sensitivity with a maximum signal amplitude of about 4 V. Compared with the sensors mentioned above installed on most commercial harvesters and sensors developed by Ni et al [ 21 ]. which attenuation time was about 1 s, and the maximum signal amplitude was less than 1.2 V, the sensitivity and detection speed of the sensor were both greatly improved.…”
Section: Development Of the Grain Impact Sensormentioning
confidence: 97%
See 1 more Smart Citation
“…This type of sensor increase not only the signals of the grain cleaning loss but also provide consistent sensitivity for the sensitive element stable performance, and high signal to noise ratio were the key characteristics of the sensor [61] 5 Pressure sensor…”
Section: Piezoelectric Crystal Sensormentioning
confidence: 99%